Predicting Counterproductive Work Behaviors: Examining the Role of Spiritual Intelligence and Personality Traits in Public and Private Sector Organizations - Jain, Neha; Rawat, Anushri (Journal of Applied Business and Economics, 2024)
Counterproductive work behaviors are intentional and harmful behaviors directed either towards the organization or towards its people. This study attempts to examine the role of two antecedent variables, spiritual intelligence (SQ), and personality based on the Big Five Personality dimensions (extraversion, agreeableness, conscientiousness, neuroticism and openness) in predicting the occurrence of counterproductive work behaviors. Two dimensions of counterproductive work behaviors: rating and self-indulgence were used in this study based on the tool developed by Jain & Singh (2020). A sample of 351 employees working in both public (170) and private (181) sector organizations in India was taken for the purpose of the study. Mean, correlational analysis and multiple hierarchical regressions were carried out to test the hypotheses. Significant results were found for both personality and spiritual intelligence (SQ) in predicting counterproductive work behaviors across both public and private sector organizations. The two antecedent variables significantly improved the model's predictive power, for both public and private sector organizations, though to a lesser extent in the private sector. No difference was found based on gender.